The effect of touchdown kinematics on forward acceleration in the skeleton push start - Zedler, M.; Schenk, C.; Braunstein, B.; Potthast, W.; Goldmann, J. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Producing forward acceleration in a bent-over position while pushing a sled is poorly understood. Therefore, the purpose of this study was to investigate body and segment orientation of 16 elite skeleton athletes for the ground contacts 1 to 3 after the start and after 15 m as well as to quantify their relation to forward acceleration. Kinematic and kinetic data were recorded indoor on an athletics track whilst the athletes were pushing a sled dummy along guiding rails. Trunk and thigh orientation remained similar during the acceleration phase, while changes in touchdown kinematics originated from the shank and foot segment. Variance in forward acceleration could be sig. explained by shank orientation (R²adj = 0.84). Consequently, training interventions to modify shank